The Importance of Industrial Internship Programme in Engineering Education: Some Critical Success Factors - Abdul Karim, Z. A. (2007)
Universiti Teknologi PETRONAS (UTP), a private university has made it compulsory for its undergraduate students to undergo an eight-month-internship program prior to their completion of studies. As the only university in Malaysia which offers a longer internship program, it is crucial that a study is carried out to investigate the students’ perception regarding the effectiveness of the program. Thus, the objectives of this study are two fold: i. to gauge the student’s perception of the importance of internship program ii. to examine the significance of the following critical success factors for an effective industrial internship program: pre-placement operations and initiatives, the commitment and efficiency of the program administrator and the commitment and support given by the host company. Data was gathered through a survey questionnaires distributed to student of the January 06 batch upon their return from the 8-month internship. These results were than tabulated and analysed using the SPSS software The results showed that the student rated highly on the experience and skills gained during the industrial internship. The students also believed that the pre-placement operations, the administration of the program and the host company are important factors in ensuring the success of the industrial internship program. The implications of this study will point towards developing a more effective internship program.